Words as Readymade: Mina Loy's Verbal Portraiture of "Gertrude Stein" and "Joyce's Ulysses". Issue 1 (16th June 2022) - Wang, Bowen
Abstract: Between 1919 and 1930, Mina Loy created a series of pictorial and poetic portraits of her artistic contemporaries: from pen-ink sketches such as Constantin Brancusi, Carl Van Vechten, Jules Pascin, Marianne Moore, to linguistically innovative verses like "'Joyce's Ulysses, " "Gertrude Stein, " "Nancy Cunard, " and a note "William Carlos Williams." In interacting with avant-gardists of her time, Loy explored new patterns of expression as an alternative to literary and cultural conventions. This paper will thus investigate the use of readymade words in two of Loy's artist-portrait poems depicting Gertrude Stein and James Joyce. Her verbal portraits do not merely offer the reader a poetic profile of modernist artists and their formal experimentation. It will be demonstrated at the end of this paper that, by treating the word as readymade, Loy and her portrayed writers are able to articulate a different form of language that is more fluid, plastic, and performative.